2016
DOI: 10.1186/s12879-016-1488-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Hepatitis C virus 3a in Peshawar

Abstract: BackgroundThe purpose of this study was to explore molecular epidemiology of HCV genotype 3a in Peshawar based on sequencing and phylogenetic analysis of Core region of HCV genome.MethodsChronically infected Hepatitis C virus infected patients enrolled under the Prime Minister Hepatitis C control program at three Tertiary care units of Peshawar [Khyber Teaching Hospital Peshawar, Lady Reading Hospital Peshawar, Hayat Abad Medical Complex Peshawar] were included in this cross sectional observational study. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…This higher percentage indicates a new shift in HCV epidemiology, although the presence of genotype 1a and 1b has been reported by other studies conducted in Pakistan (16). A more recent study conducted in the Khyber Pakhtunkhwa province has also reported a shift the distribution of HCV types with higher percentage of HCV 1b or its mixed infections (21).…”
Section: Percent Of Genotypesmentioning
confidence: 49%
“…This higher percentage indicates a new shift in HCV epidemiology, although the presence of genotype 1a and 1b has been reported by other studies conducted in Pakistan (16). A more recent study conducted in the Khyber Pakhtunkhwa province has also reported a shift the distribution of HCV types with higher percentage of HCV 1b or its mixed infections (21).…”
Section: Percent Of Genotypesmentioning
confidence: 49%
“…In the present study, genetic relatedness with local isolates points to the prior presence of similar types in other parts of Pakistan. Recently, Gul et al (17) described the evolutionary analysis of HCV genotype 3a isolates from Peshawar.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C Virus genotype 3a is more prevalent in Pakistan, and few studies were con-ducted on complete core protein sequences and phylogenetic analysis in the north-west of Pakistan. Studies performed locally revealed a prevalence of genotype 3a from 26% to 45% (17,18). According to a national survey conducted in 2007, 4.8% of the Pakistani population was infected with HCV, which corresponds to nearly 9.9 million of overall HCV cases in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…A baseline investigation along with genotyping and viral load quantification was done. HCV RNA was detected using quantitative PCR (Q-PCR) according to the operating manual of the test kit (Qiagen, Germany) followed by HCV genotyping [36].…”
Section: Samples Collection and Processingmentioning
confidence: 99%
“…The P value (< 0.05) was labeled significant. HCV genotype determination was carried out as described earlier [36]. For HCV genotype determination, RNA extraction was carried according kit protocol.…”
Section: Samples Collection and Processingmentioning
confidence: 99%